The effect of equity structure and influence factors on China's banking cyclical behavior and monetary policy - Crentsil Kofi Agyekum (China Finance and Economic Review, 2017)
Several years ago, there were crises on mortgage that resulted in a serious thread on financial systems in the United States of America and other developed and developing countries. However, some scholars are of the view that the pro-cyclical nature of the bank led to this serious incident. In this study, we focus on China's bank lending behavior whether it falls within the cyclicality of the banking practices. The study realized that credit distributions were still the managerial way of for transferring government monetary policy. It is not however the actual reasons behind the China's bank counter-cyclical lending. State-owned financial firms within higher ownership are of no doubt of likely to be counter cyclical. Some school of thought are with the view that compared to developed countries, state-owned banks play a major decisions in other developing countries such as Brazil, and they believe that the well performances of this nations are adhering to the financial crises that are highly related to the state-owned banks. For example in China, commercial banks are the main embodiment of China's financial institutions. It is believed that most of these banks have very strong support by the central government and that makes clients pay more attention to their well-being thus implementing the states macroeconomic policies and resisting the financial crises. The study based on other existing researches will take the government monetary policy and commercial banks equity structure into a frame work and under search how they influence the cyclical China's commercial bank lending behavior and project other possible effects for regulatory bodies to take it into account when making a decision.
Keywords: 330; Monetary policy; Shareholder structure; Lending behavior; Counter-cyclicality